Proceedings of the ACM Symposium on Applied Perception 2014
DOI: 10.1145/2628257.2628261
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two cost-differentiated virtual reality systems for perception and action tasks

Abstract: Recent advances in technology and the opportunity to obtain commodity-level components have made the development and use of three-dimensional virtual environments more available than ever before. How well such components work to generate realistic virtual environments, particularly environments suitable for perception and action studies, is an open question. In this paper we compare two virtual reality systems in a variety of tasks: distance estimation, virtual object interaction, a complex search task, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 45 publications
(69 reference statements)
4
30
1
2
Order By: Relevance
“…However, none of those cues is singularly responsible for the underperception that characterizes distance perception in VEs. Recent research using newer HMDs has reported nearveridical judgments of egocentric distance (Li, Zhang, & Kuhl, 2014;Young, Gaylor, Andrus, & Bodenheimer, 2014), but the reason for the reported differences between HMDs is unknown. Distance judgments in the VE conditions of Li et al (2013;experiment 2) were larger than those in the current experiment.…”
Section: Resultsmentioning
confidence: 99%
“…However, none of those cues is singularly responsible for the underperception that characterizes distance perception in VEs. Recent research using newer HMDs has reported nearveridical judgments of egocentric distance (Li, Zhang, & Kuhl, 2014;Young, Gaylor, Andrus, & Bodenheimer, 2014), but the reason for the reported differences between HMDs is unknown. Distance judgments in the VE conditions of Li et al (2013;experiment 2) were larger than those in the current experiment.…”
Section: Resultsmentioning
confidence: 99%
“…This poster abstract supplements that study results with an additional HMD for evaluation of egocentric distance estimation task, an Nvis SX111. We find that performance of the Nvis SX111 is comparable to that of the Nvis SX60 in Young et al [2014], which was significantly more compressed than the Oculus Rift.…”
Section: Introductionmentioning
confidence: 73%
“…A previous study, Young et al [2014], explored comparisons between cost-differentiated head-mounted displays for the evaluation of various perception and action tasks. One of the comparisons in that work was egocentric distance estimation comparison using an Nvis SX 60 head-mounted display (HMD) and an Oculus Rift.…”
Section: Introductionmentioning
confidence: 99%
“…For each concept, the six questions were divided into easy (2), medium (2) and hard (2). At evaluation time, the student is provided with three questions, one at each difficulty level.…”
Section: Software Description (Its)mentioning
confidence: 99%
“…Beyond understanding how people perceive this mix of virtual and real objects, researchers must understand how the composition of the environment influences not only perceptual factors, but how these factors contribute to higher cognitive processes. Virtual Reality (VR) has successfully provided an environment for training users on perception and action tasks [2]. For example, novice pilots often train in simulators that are designed to focus on cognitive tasks to prevent unnecessary distraction from irrelevant controls [3].…”
Section: Introductionmentioning
confidence: 99%